The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12885-021-08589-8
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-coated leukocytes to kill circulating tumor cells in the flowing blood from prostate cancer patients

Abstract: Background Radical surgery is the first line treatment for localized prostate cancer (PC), however, several studies have demonstrated that surgical procedures induce tumor cell mobilization from the primary tumor into the bloodstream. Methods The number and temporal fluctuations of circulating tumor cells (CTC), cancer associated fibroblasts (CAF) and CTC cluster present in each blood sample was determined. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, to our knowledge, the largest prospective-retrospective study on 594 metastatic breast cancer patients indicated that it is the number of CTCs, regardless of ''cluster status,'' that causes the dismal prognosis (Paoletti et al, 2019). Furthermore, certain treatment regimens can cause a release of CTC clusters without causing an increase in metastases formation (Mohme et al, 2017;Ortiz-Otero et al, 2021). Nevertheless, CTC clusters may additionally have other negative consequences for patient outcome by causing cerebral infarctions and lung emboli (Feinauer et al, 2021;Hong et al, 2016).…”
Section: Review Llmentioning
confidence: 99%
“…However, to our knowledge, the largest prospective-retrospective study on 594 metastatic breast cancer patients indicated that it is the number of CTCs, regardless of ''cluster status,'' that causes the dismal prognosis (Paoletti et al, 2019). Furthermore, certain treatment regimens can cause a release of CTC clusters without causing an increase in metastases formation (Mohme et al, 2017;Ortiz-Otero et al, 2021). Nevertheless, CTC clusters may additionally have other negative consequences for patient outcome by causing cerebral infarctions and lung emboli (Feinauer et al, 2021;Hong et al, 2016).…”
Section: Review Llmentioning
confidence: 99%
“…In a word, CAFs can protect CTC clusters through various mechanisms ( 121 ). More importantly, studies have shown that the level of CTC clusters and CAFs can be used as bio–markers to predict cancer recurrence ( 122 ). This shows that targeting CAF–CTC clusters has certain clinical significance.…”
Section: Heterotypic Circulating Tumor Cell Clustersmentioning
confidence: 99%
“…They observed that 2/15 patients experienced cancer recurrence within 2 months after primary tumor resection, and levels of individual CTCs and CTC clusters were increased in these patients at the time of surgery or after surgery. Moreover, the levels did not normalize after 2 weeks, suggesting levels of individual CTCs and CTC clusters vary considerably in PCa progression [ 22 ]. Additionally, combining CTC clusters with routine single CTC detection exhibited independent predictive value in improving prognostic stratification in mCRPC patients [ 127 ].…”
Section: Ctcs In Clinical Applicationmentioning
confidence: 99%
“…CTCs are generally referred to as either single CTCs or CTC clusters, with the latter considered to have a 23- to 50-fold greater metastatic potential [ 12 , 19 ]. Studies suggest that a CTC cluster contains at least 2 tumor cells (and up to 100) and several non-malignant cells including but not limited to a heterogeneous group of cells, for example, tumor-associated macrophages (TAMs), cancer-associated fibroblasts (CAFs), white blood cells, epithelial cells and platelets [ 20 , 21 , 22 , 23 , 24 , 25 ]. In contrast to single CTCs, CTC clusters show distinctive phenotypes, gene expression, and metastasis patterns, indicating unique biological properties in neoplasm metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation